Efektivitas Penghentian Sengketa Informasi Publik yang Tidak Dilakukan dengan Itikad Baik di Komisi Informasi Provinsi Banten - Odi Salsabilla Kirana Fitri Sudrajat; Ikomatussuniah Ikomatussuniah; Rila Kusumaningsih (Pusat Riset dan Inovasi Nasional, 2026)
Public information disclosure is a manifestation of open and accountable government which is the basis for publik information requests. Everyone has the right to obtain public information through the mechanism of requesting information from public bodies. The problem that arises is that some information requessts are not made in good faith thereby failing to reflect the purpose of public information disclosure as a means of monitoring government performance. To adress this issue there is a mechanism to terminate the resolution of such information disputes in accordance with applicable laws and regulations. This study aims to determine the effectiveness of terminating informastion disputes that are not conducted in good faith and the obstacles in its implementation. The results of the study indicate that the termination of informastion disputes that are not conducted in good faith is not yet effective due to factors that influence the effectiveness of the law in society not being fulfilled including legal factors, societal factors, and cultural factors. The obstacles faced in the implementation of the termination of public information disputes that are not conducted in good faith include legal enforcement mechanism, public information management, and understanding of public information transparency. The effectiveness of a law is determined by the overall elements supporting its enforcement so it is hoped that the implementation of the termination of publik information disputes does not violate human rights and citizens’ rights.